Analisis Kemampuan Pemecahan Masalah Matematis Siswa SMP Ditinjau dari Adversity Quotient pada Materi SPLDV - Hadat Adi Purwa; Eyus Sudihartinih (Jurnal Ilmiah Pendidikan Matematika Al Qalasadi, 2024)
This research aims to describe the mathematical problem-solving abilities of junior secondary level students in terms of each student's adversary quotient level. This type of research is qualitative research with descriptive methods. The data collection techniques used in this research were tests, questionnaires, and interviews. The participants in this research were three junior high school students in Bogor Regency. The instruments used in this research were an adversity quotient questionnaire, mathematical problem-solving ability test questions, and interviews. The results of the research show that there are several relationships between the adversity quotient and students' mathematical problem-solving abilities. Climbers, campers, and quitters-type students have high, medium, and moderate mathematical problem-solving skills. However, the interview results show that quitters tend to give up easily when faced with complex problems. So that future researchers should study these findings further and increase the number of participants so that the research results are more valid.